Health Outcomes in Acromegaly: Depression and Anxiety are Promising Targets for Improving Reduced Quality of Life - Geraedts, Victor Jacobus; Dimopoulou, Christina; Auer, Matthias; Schopohl, Jochen; Stalla, Günter Karl; Sievers, Caroline (Frontiers in Endocrinology, 2015)
IINTRODUCTION. Remission criteria of acromegaly are based on biochemical variables, i.e. normalization of increased hormone levels. However, the established reduction in Quality of Life (QoL) is suggested to be independent of biochemical control. The aim of this study was to test which aspects predict Qol best in acromegaly. METHODS/Design. This is a prospective cohort study in 80 acromegalic patients, with a cross-sectional and longitudinal part. The main outcome measure was health-related quality of life (QoL), measured by a generic and a disease-specific questionnaire (the SF-36 and AcroQol). Main predictors were age, gender, biochemical control, disease characteristics, treatment modalities and psychopathology. RESULTS. Our cohort of 80 acromegalics had a mean age 54.7 ± 12.3 years with an average disease duration of 10.8 ± 10.0 years. Ratio macro-/microadenoma was 54/26. In adjusted mixed method models, we found that psychopathology significantly predicts QoL in acromegaly (in models including the variables age, gender, disease duration, tumor size, basal hormone levels, relevant treatment modalities and relevant comorbidities), with a higher degree of psychopathology indicating a lower QoL (depression vs. AcroQoL: B=-1.175, p<0.001, depression vs. SF36: B=-1.648, p<0.001, anxiety vs. AcroQoL: B=-0.399, p<0.001, anxiety vs. SF36: B=-0.661, p<0.001). The explained variances demonstrate superiority of psychopathology over biochemical control and other variables in predicting QoL in our models. DISCUSSION. Superiority of psychopathology over biochemical control calls for a more extensive approach regarding diagnosing depression and anxiety in pituitary adenomas to improve QoL. Depressive symptoms and anxiety are modifiable factors that might provide valuable targets for possible future treatment interventions.